Emerging Resistive Switching Memories - Ouyang, Jianyong (SpringerBriefs in Materials, 2016)
This brief describes how non-volatile change of the resistance , due to the application of electric voltage allows for fabrication of novel digital memory devices. The author explains the physics of the devices and provides a concrete description of the materials involved as well as the fundamental properties of the technology. He details how charge trapping, charge transfer and conductive filament formation effect resistive switching memory devices.